2018
DOI: 10.1249/mss.0000000000001668
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Interval or Continuous Moderate Exercise: A 24-Week Pilot Trial

Abstract: This pilot intervention was successful in increasing, and maintaining, free-living MVPA over a 24-wk period in individuals at high risk of T2D. Speculation that HIIT is inappropriate or unattainable for overweight individuals at high risk of T2D may be unfounded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…HIIT has been reported to be safe, even in selected high‐risk populations with cardiovascular disease, but many HIIT protocols for clinical populations with elevated cardiovascular risk have been modified to be less strenuous and some authors advocate to be cautious when prescribing HIIT to patients with cardiometabolic disease . A recent large‐scale study concluded that HIIT feasibility in heart failure patients remains unsolved, while a pilot trial in obese, middle‐aged subjects (mostly women) concluded that HIIT may be appropriate and attainable for this population …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIIT has been reported to be safe, even in selected high‐risk populations with cardiovascular disease, but many HIIT protocols for clinical populations with elevated cardiovascular risk have been modified to be less strenuous and some authors advocate to be cautious when prescribing HIIT to patients with cardiometabolic disease . A recent large‐scale study concluded that HIIT feasibility in heart failure patients remains unsolved, while a pilot trial in obese, middle‐aged subjects (mostly women) concluded that HIIT may be appropriate and attainable for this population …”
Section: Discussionmentioning
confidence: 99%
“…65 A recent large-scale study concluded that HIIT feasibility in heart failure patients remains unsolved, 66 while a pilot trial in obese, middle-aged subjects (mostly women) concluded that HIIT may be appropriate and attainable for this population. 67…”
Section: Perspectives and Potential Implementation Of Hiitmentioning
confidence: 99%
“…The aim of this study was to a) characterize the content of an exercise-based intervention for individuals at risk of type 2 diabetes, Small Steps for Big Changes (Small Steps) using a common vocabulary as set out by the 93-item Behavior Change Technique Taxonomy (BCTTv1) Findings from the Small Steps pilot study revealed a significant increase in physical activity adherence at 6-month follow-up for both the high intensity interval training intervention (HIIT) and the moderate intensity continuous training intervention (MICT), however adherence was greater in HIIT than MICT with a 53 and 34-minute increase in moderate to vigorous physical activity of 10-minutes or greater from baseline to 24-weeks respectively [27]. In addition, increases in self-efficacy, self-regulatory efficacy and outcome expectations were seen post intervention with self-efficacy beliefs remaining higher at 6-month follow-up to a similar extent between conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Mapping BCTs onto the theoretical domains framework is necessary to capture these additional evidence-based mechanisms of action that move beyond SCT given the explicit inclusion of techniques known to positively influence physical activity behavior. Initial findings from a pilot of the Small Steps program showed significant increases in self-efficacy, outcome expectations, and higher engagement in moderate-vigorous physical activity at 1-and 6-months post-program completion [26,27]. Reporting the outcomes of Small…”
mentioning
confidence: 99%
“…The FITT characteristic most commonly manipulated is “time” . In particular, high‐intensity interval training (HIIT) has become popular, not least because HIIT training tends to be of shorter duration and the most commonly cited barrier to exercise participation is a lack of time . However, HIIT also manipulates time and removal of a barrier to exercise, either perceived or real, may not translate to increased adherence.…”
Section: Introductionmentioning
confidence: 99%